What Happens When the United States Stops Taking in Refugees?. (May 2019) - Fee, Molly; Arar, Rawan
Most of the world's 25.4 million refugees have been displaced for five or more years. A sharp curtailment in refugee arrivals to the United States, then, isn't just a national decision, but a global disruption.